Pembuatan Sistem Informasi Peminjaman dan Pengembalian Buku di Perpustakaan SMK Kosgoro 1 Kota Solok dengan Menggunakan Microsoft Visual Basic 2010 - Syahputri, Wira; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The steps - steps in the manufacture of information system of borrowing and returning books at the Library SMK Kosgoro 1 Solok with Microsoft Visual Basic 2010 are as follows: First, designing procedures or groove of the new system to be created; Second, create a new project in Microsoft Visual Basic 2010; Third, create a form that consists of the main menu, login form, the form members, form books, borrowing books form, and form the return of books; Fourth, fill in the code on each button on each form and then save the project and run it. From the results of the manufacturing information system of borrowing and returning books by using Microsoft Visual Basic 2010 is expected to address the weaknesses - weaknesses that often occurs in vocational Library Kosgoro 1 Solok and is expected to assist librarians in the process of borrowing and returning books quickly and is also expected to accelerate in the preparation of the loan and return books and automatically calculating the cost of delay. Keywords: borrowing and returning books, visual basic 2010